The RNA-binding protein AKAP8 suppresses tumor metastasis by antagonizing EMT-associated alternative splicing - Xiaohui Hu (Nature Portfolio, 2020)
Splice isoform switching regulated by the heterogeneous nuclear ribonucleoprotein M (hnRNPM) induces EMT and metastasis. Here, the authors report that AKAP8 is a metastasis suppressor that inhibits the splicing activity of hnRNPM and antagonizes genome-wide EMT-associated alternative splicing to maintain epithelial cell state.